Pengaruh Latihan Drill Menggunakan Sasaran Dinding terhadap Peningkatan Kemampuan Passing Bawah Peserta Ekstrakurikuler Bola Voli SMP Negeri 1 Tambak - Mokhamad Parmadi; Rangga Putra Yanuar (Mathematics Education Study Program, 2025)
This study aims to determine the effect of drill training using wall targets on improving basic volleyball underpassing techniques in extracurricular participants at SMP Negeri 1 Tambak. The data collection instrument in this study used the Volleyball Skills Test for Ages 13-15 Years. The subjects of this research were extracurricular volleyball participants at SMP Negeri 1 Tambak, consisting of 20 students (12 boys and 8 girls). The results of instrument testing showed validity of 0.733 and reliability of 0.758. Meanwhile, the normality results show a p value (Sig.) greater than 0.05, so it can be concluded that the data is normally distributed. The results of this study showed a significant increase in down-passing ability. The average student score increased from 19.85 to 36.1. The increase in the lower passing ability of extracurricular volleyball participants at Tambak 1 State Middle School resulted in a mean difference between the pre test and post test of 16.25 and t count 7.960 > t table 2.093. The drill method using a wall target has a significant impact on the bottom passing ability of volleyball extracurricular participants at SMP Negeri 1 Tambak.